Effects of surface topology and texture on exchange anisotropy in NiFe/Cu/NiFe/FeMn spin valves - Park, CM; Min, KI; Shin, KH (AMER INST PHYSICS, 1996)
We have investigated the effects of texture and interfacial roughness on the exchange anisotropy in NiFe/Cu/NiFe/FeMn spin valves with different buffer layers (no buffer, Cu, or FeMn) on Si(100) or Si(111) substrates by magnetron sputtering. The crystalline structure, surface topology, and exchange anisotropy field (H-ex) were characterized. The exchange anisotropy was established all in (111), (200), and (220) textured samples and there was no systematic relationship between the type of texture and H-ex. However, it was found that H-ex increased as the surface roughness decreased. The results lead us to believe that interfacial roughness rather than crystallographic texture controls the development of the exchange anisotropy. (C) 1996 American Institute of Physics.